The impact of the Wingate test on anaerobic power in the lower limbs of athletes with varied duration and load - Liu, Y.; Yan, J.; Gong, Z.; Liu, Q. (Frontiers in Physiology, 2025)
Introduction: This study investigates the effects of Wingate anaerobic test (WAnT) on anaerobic capacity (AC) at different duration (20, 30, 40, 45 s) and resistance load (7.5%Body Mass (BM), 8.5%BM, 9.5%BM, 10.5%BM).